Solar Tracking System With Automatic Panel Cleaning - Ngu, Jotham Ong Hu (Universiti Malaysia Sarawak, (UNIMAS), 2020)
The growth of solar power technology across every continent in the world is very fast and steady and in the near future, almost every country will have a history to tell about the numerous benefits of going solar. However, solar panels have a low energy capturing efficiency compared to other renewable energy due to a big loss in sun tracking loss and soiling effect. Thus, this project has been carried out with the goal to tackle both problems in solar panel with a proposed system. A combination of solar tracking system and panel cleaning system has been designed and a prototype of the system has been built to improve the efficiency of a solar panel in energy capturing process. Arduino has been used for the implementation of the prototype. Moreover, an experiment has been carried out to make comparison between the efficiency of a solar panel fixed on the proposed system and a static solar panel. The results reveal the improvement of the efficiency of the solar panel which shows the practicality and the significance of the project in solar energy industry